Relationships, Learning, and Motivation for One Virtual Literacy Camp during the COVID-19 Pandemic - Caitlin Spears; Heather D. Young (Educational Considerations, 2022)
This article focuses on one university literacy camp for kindergarten through sixth grade students that shifted from traditional in-person instruction to a virtual setting during the COVID-19 pandemic. The change from an in-person camp to a virtual camp setting created an opportunity for research in investigating students’ attitudes towards literacy, literacy learning, and participation within the newly formatted virtual literacy camp. Twenty-six kindergarten through sixth grade students were interviewed at the beginning and conclusion of a semester-long literacy camp regarding their attitudes toward learning and participation in the literacy camp. Throughout the data, researchers noted the theme of relationships as being prevalent with many participants sharing thoughts specifically in light of the lack of outside interaction during this more isolated era of time. The relationships built between the tutors and the students in this virtual camp were vital to the attitudes and the learning of these study participants. This study provides further direction for supporting students in a virtual literacy clinic setting.
Keywords: Relationships; Learning; Motivation; Literacy; Literacy Clinic; Virtual Learning; Social-Emotional Learning; COVID-19; Attitudes